Isolation and Characterization of Stem Cells Derived by Human Dental Pulp from Harvest Based in Rotary and Manual Techniques used in Endodontic Therapy - Weiss, Jairo Barros; Gonçalves, Fernanda da Silva; Maranduba, Carlos Magno da Costa; de Resende, Leandro Marques; do Carmo, Antonio Marcio Resende (Brazilian Dental Science, 2020)
Objective: The aim of this study was to evaluate the impact on the isolation and characterization of stem cells from pulp tissues obtained through rotary instrumentation techniques compared to the manual technique. Material and Methods: Thirty permanent teeth were included, 15 of which were instrumented with rotational technique (Protaper SX) and other 15 with manual technique. Cells obtained were characterized by flow cytometry and proliferation was evaluated by the MTT assay. The plasticity was evaluated for adipogenic, osteogenic and odontogenic differentiations. Results: Cells isolated from the pulp of permanent teeth, by manual techniques, presented fibroblast morphology and were able to differentiate successfully. All lineages expressed CD29, CD73, CD90, CD105, CD146, CD166 and were negative for CD31, CD34 and CD45. MTT assay showing significantly increased proliferation of hDPSCs in 5 and 7 days of the culture. Conclusion: The present study demonstrated that manual instrumentation technique is one of the best candidates to harvest dental pulp tissue as the dental stem cell source due to ability effective expanded with less tissue invasion. The technique of rotational instrumentation proved to be very harmful to the tissues of the dental pulp, and we can’t obtain cells using this technique. Keywords: Root Canal Therapy; Pulpectomy; Anatomy and Histology; Stem Cell.